Ni/Graphdiyne composites inhibit dendrite growth in lithium metal anodes. (1st February 2023) - Kang, Huifang; Hua, Binchang; Gao, Peiyan; Luo, Shuang; Yao, Hurong; Sun, Yuanyuan; Xu, Lanqing; Zheng, Yongping; Li, Jiaxing
Highlights: Synergies effect enhance electrochemistry performance in Ni/GDY composite material. A very low overpotential of 12 mV archive in Ni/GDY composite. The cycle efficiency archive 98.5%, and have a cycle time of up to 2200 h in Ni/GDY. Abstract: The growth of lithium dendrites during repeated deposition or dissolution is a key issue that inhibits lithium metal anodes for high energy density batteries. Here, we demonstrate nickel-anchored graphdiyne materials by solvothermal method on three-dimensional copper foam and apply them to Li metal deposition and stripping. The graphdiyne has a very high Li storage capacity, but poor Li affinity. On the other hand, Ni is highly lithiophilicity and the rich nanoporous structure of graphdiyne provides a stable Li deposition interface, enabling high-efficiency and high-capacity Li deposition and stripping. Ni-anchored graphdiyne modified copper foam substrate can achieve high-area, high-rate dendrite-free Li deposition and stripping. The deposition and stripping of 1 mA h cm −2 of lithium at a current density of 1 mA cm −2 show an overpotential of about 12 mV, high cycle efficiency of 98.5%, and a cycle time of up to 2200 h. The cycle efficiency can reach 98% at higher current density and higher lithium deposition and stripping amount. We assemble a full battery with Ni/GDY@Li using LiFePO4 as the cathode material, showing excellent capacity and cycling stability. Graphical abstract: Image, graphical abstract